Waterproofing part and electronic device equipped with same, waterproofing method using insert molding, and waterproofing method for electronic device

JP7636976B2Active Publication Date: 2025-02-27KURARAY CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021102489
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-21
Publication Date
2025-02-27
Estimated Expiration
2041-06-21

AI Technical Summary

Benefits of technology

【0012】 本発明により、リフロー工程等の加熱工程を経ても十分な防水性を有し、なおかつ難燃性を有する、インサート成形体である防水部品及びそれを備えた電子機器を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636976000014
    Figure 0007636976000014
  • Figure 0007636976000015
    Figure 0007636976000015
  • Figure 0007636976000016
    Figure 0007636976000016
Patent Text Reader

Abstract

To provide a waterproof component that is an insert molding, having sufficient waterproofness even after a heating process such as a reflow step, and also having fire retardancy, and an electronic apparatus including the same.SOLUTION: A waterproof component is an insert molding composed of a thermoplastic resin composition and a metal component, the thermoplastic resin composition containing a thermoplastic resin (A), inorganic reinforcement (B), polyolefin (C1) and / or long-chain fatty acid compound (C2), at least one phosphinate (D) represented by formula (I) or formula (II), and phosphite (E). Relative to 100 pts.mass of the thermoplastic resin (A), the inorganic reinforcement (B) is 8-130 pts.mass, the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3-40 pts.mass, the phosphinate (D) is 25-40 pts.mass, and the phosphite (E) is 2-15 pts.mass in content. There is also provided an electronic apparatus including the same.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a waterproof part, an electronic device including the same, a waterproofing method using an insert molded product, and a waterproofing method for electronic devices. [Background technology]

[0002] In recent years, electronic devices such as smartphones are increasingly required to be waterproof. The external connection terminals of such electronic devices are typically composites of resin or resin composition and metal parts, and the metal parts are often exposed to the outside, making waterproofing the joint surface between the resin or resin composition and the metal a problem. At the same time, as a manufacturing method for printed circuit boards with bonded electronic parts, the use of surface mounting, in which lead-free solder paste is printed on a printed circuit board, electronic parts are mounted on it, and then the board is heated in a reflow furnace at about 260°C at which the lead-free solder melts, is becoming more widespread. Surface mounting can achieve miniaturization of printed circuit boards and improved productivity, but the mounted parts are subjected to stress in the reflow process and the subsequent cooling process according to the difference in expansion and contraction properties between the metal parts and the resin or resin composition, which tends to cause small gaps between the metal parts and the resin or resin composition, making it difficult to maintain waterproofing. For this reason, conventional methods for waterproofing such external connection terminals include a method using a sealing material such as an elastomer, and surface modification by chemical etching of the metal surface during insert molding (Patent Documents 1 and 2, etc.). However, there are problems such as the inability to complete the part in one process and increased costs due to the need to attach the elastomer and etch the metal surface. In view of this, there has been proposed a method for manufacturing a waterproof part by insert molding, in which a resin or a resin composition is injected onto a metal part inserted into a mold and the parts are joined together (Patent Documents 3 to 6, etc.). For example, Patent Document 3 discloses a polyamide resin composition containing a rubber polymer and a dendritic polyester, and a resin-metal composite made of the resin composition. Patent Document 4 discloses a polyamide resin composition containing a specific branched molecule, a filler, an impact resistance improver, and a resin-metal composite made of the resin composition. Patent Document 5 discloses a polyamide resin composition containing one or more additives selected from the group consisting of a magnesium compound, glass fiber, a fatty acid metal salt, an amide group-containing compound, and a maleic anhydride group-containing compound, and a molded article containing the resin composition. Patent Document 6 discloses a waterproof part that is an insert molded article made of a thermoplastic resin composition containing a thermoplastic resin, an inorganic reinforcing material, and a polyolefin or a long-chain aliphatic acid compound.

[0003] In the field of electrical and electronic components, flame retardancy is often required for components, and in many cases it is necessary to achieve a rating of V-0 in the UL94 standard of Underwriters Laboratories. Traditionally, materials containing brominated flame retardants have been commonly used as heat-resistant polyamides for forming electrical and electronic components. However, due to the increasing awareness of the environment in recent years, the use of some raw materials containing harmful lead, cadmium, etc. is being restricted. There is also a tendency to avoid the use of compounds containing halogens, such as brominated flame retardants, regardless of the evaluation results of their safety and actual environmental impact, and there is an increasing demand for halogen-free flame-retardant polyamides. There are several known halogen-free flame retardants that can be mixed into polyamides. However, flame retardants that are mixed into heat-resistant polyamides with high melting points are required to have high flame retardancy as well as high heat resistance that can withstand high temperatures during melt-kneading in the manufacture of polyamide resin compositions and during molding in the manufacture of molded products. This tendency is particularly noticeable in electrical and electronic components that undergo the reflow process in the surface mounting process. Phosphinate salts are known as halogen-free flame retardants having high flame retardancy and heat resistance. For example, a flame-retardant polyamide molding material containing a specific polyamide having diamine units mainly composed of alicyclic diamine units and a phosphinate salt is known (e.g., Patent Document 7). In addition, a resin composition containing a specific semi-aromatic polyamide, polyphenylene ether, and a phosphinate salt is known (e.g., Patent Documents 8 and 9). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-33155 A [Patent Document 2] International Publication No. 2010 / 107022 [Patent Document 3] JP 2013-249363 A [Patent Document 4] JP 2014-141630 A [Patent Document 5] JP2015-36415A [Patent Document 6] International Publication No. 2020 / 175390 [Patent Document 7] Japanese Patent Publication No. 51-63859 [Patent Document 8] JP 2007-182550 A [Patent Document 9] JP 2007-182551 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the resins used in the resin compositions of Patent Documents 3 and 4 above have low heat resistance, and may deform or melt during the reflow process when applied to surface mounting. In addition, the addition of a rubber-like polymer component may reduce heat resistance and mechanical strength, or increase burrs. In Patent Document 5, water resistance is evaluated as insulation after moisture absorption, but water penetration is not evaluated. Furthermore, none of the above patent documents suggests compatibility between waterproofness and flame retardancy. In general, when flame retardancy is imparted to a resin composition, mechanical properties, fluidity, and other properties tend to decrease, and metal adhesion also tends to decrease. If the metal adhesion of the resin composition decreases, sufficient waterproofness may not be obtained. Therefore, there remains a problem of achieving compatibility between waterproofness and flame retardancy in a resin composition that can pass the reflow process of surface mounting.

[0006] That is, an object of the present invention is to provide a waterproof part which is an insert-molded body that has sufficient waterproofness even after undergoing a heating process such as a reflow process and also has flame retardancy, and an electronic device equipped with the waterproof part. [Means for solving the problem]

[0007] As a result of intensive research, the inventors have found that in a waterproof part, which is an insert molded body made of a thermoplastic resin composition and a metal part, by adding specific amounts of a specific olefin-based compound, a specific phosphinate, and a specific phosphite to the thermoplastic resin used, the waterproofness after the reflow process can be improved and flame retardancy can also be imparted. Based on this finding, the inventors have conducted further research and completed the present invention.

[0008] The present invention relates to the following [1] to

[20] . [1] A waterproof part which is an insert molding made of a thermoplastic resin composition and a metal part, The thermoplastic resin composition comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the following formula (I) or the following formula (II), and a phosphite (E), A waterproof part, wherein the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A).

[0009] [ka]

[0010] [ka]

[0011] [In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n.] [2] The waterproof part according to [1], wherein the polyolefin (C1) is a polyolefin that has been subjected to at least one of maleic acid modification, oxidation, and polar monomer modification. [3] The waterproof part according to [1] or [2], wherein the long-chain fatty acid compound (C2) is a long-chain fatty acid compound having 15 or more carbon atoms. [4] The waterproof part according to any one of [1] to [3], wherein the long-chain fatty acid compound (C2) is a long-chain fatty acid compound having 15 or more carbon atoms and which has been subjected to at least one of the following modification treatments: esterification, maleic acid modification, and saponification. [5] The phosphite (E) is aluminum phosphite or aluminum hydrogen phosphite. [1] to [4] Either Described in Waterproof parts . [6] The waterproof part according to any one of [1] to [5], wherein the melting point of the thermoplastic resin (A) is 280° C. or higher. [7] The waterproof part according to any one of [1] to [6], wherein the thermoplastic resin (A) is at least one selected from the group consisting of polyamide, liquid crystal polymer, polyphenylene sulfide, and styrene-based polymer mainly having a syndiotactic structure. [8] The waterproof part according to any one of [1] to [7], wherein the thermoplastic resin (A) is a polyamide in which 50 to 100 mol % of diamine units are aliphatic diamine units having 4 to 18 carbon atoms. [9] The waterproof part according to any one of [1] to [8], wherein the inorganic reinforcing material (B) is at least one selected from the group consisting of glass fiber, milled fiber, wollastonite, mica, glass flakes, and glass beads.

[10] The waterproof part according to any one of [1] to [9], wherein the inorganic reinforcing material (B) is at least one type selected from glass fibers having circular cross sections and noncircular cross sections, and the peripheral length of a cross section of the glass fiber having a noncircular cross section is 1.05 to 1.8 times the peripheral length of a glass fiber having the circular cross section and having the same cross-sectional area as the noncircular cross section.

[11] A waterproof component according to any one of [1] to

[10] , which is used for an application applied to a surface mounting process.

[12] The waterproof part according to any one of [1] to

[11] , which is an external connection terminal.

[13] The waterproof part according to any one of [1] to

[11] , which is a switch.

[14] An electronic device comprising a waterproof component according to any one of [1] to

[13] .

[15] The electronic device according to

[14] , which is a portable electronic device.

[16] A thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), the phosphinate (D) in [1], and the phosphite (E), A thermoplastic resin composition is used, in which the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A). A method for waterproofing an electronic device using an insert molded article comprising the thermoplastic resin composition and a metal part.

[17] A thermoplastic resin (A), an inorganic reinforcing material (B), and a polyolefin (C1) and / or a long-chain fatty acid compound (C2), comprising the phosphinate (D) and the phosphite (E) in [1]; A thermoplastic resin composition is used, in which the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A). Use of the thermoplastic resin composition and a metal part as an insert molding for waterproofing.

[18] A method for waterproofing an electronic device, which uses the waterproof component according to any one of [1] to

[11] as an external connection terminal.

[19] A method for waterproofing an electronic device, using the waterproof component according to any one of [1] to

[11] as a switch.

[20] A thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), the phosphinate (D) in [1], and the phosphite (E), A method for producing a waterproof part, comprising insert-molding a thermoplastic resin composition, the content of which is 8 to 130 parts by mass of the inorganic reinforcing material (B), the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2), the content of the phosphinate (D) being 25 to 40 parts by mass, and the content of the phosphite (E) being 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A), with a metal part. Effect of the Invention

[0012] According to the present invention, it is possible to provide a waterproof part that is an insert-molded product that has sufficient waterproofness even after undergoing a heating process such as a reflow process and also has flame retardancy, and an electronic device equipped with the waterproof part. [Brief description of the drawings]

[0013] [Figure 1] 1 is a photograph of a sample used in a red ink test in an embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of line XX′ in FIG. 1 for explaining a red ink test of an embodiment. [Diagram 3] 1 is a photograph showing a sample for illustrating a red ink test of an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. The waterproof part of the present invention is an insert-molded article made of a thermoplastic resin composition and a metal part, The thermoplastic resin composition comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the formula (I) or the formula (II), and a phosphite (E), Relative to 100 parts by mass of the thermoplastic resin (A), the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass. By using the thermoplastic resin composition, an insert molded article consisting of a thermoplastic resin composition and a metal part has excellent waterproofness (at the joint surface between the thermoplastic resin composition and the metal), and the waterproof part has sufficient waterproofness, thereby achieving compatibility with flame retardancy. Although the reason for this is not entirely clear, it is believed that by using the thermoplastic resin composition, the polyolefin (C1) and / or the long-chain fatty acid compound (C2) melt before and after the molding process and heating process, thereby relieving stress at the bonding surface between the thermoplastic resin composition and the metal, and further, the phosphinate (D) and the phosphite (E) have good compatibility with the resin and have heat resistance sufficient to withstand the reflow process, thereby preventing the occurrence of gaps at the bonding surface between the thermoplastic resin composition and the metal.

[0015] (Thermoplastic resin (A)) The thermoplastic resin (A) used in the present invention is not particularly limited as long as it can impart the above-mentioned effects, and examples thereof include polycarbonate; polyphenylene oxide; polyphenylene sulfide (PPS); polysulfone; polyethersulfone; polyarylate; cyclic polyolefin; polyetherimide; polyamide; polyamideimide; polyimide; liquid crystal polymers such as aromatic polyesters and aromatic polyesteramides; polyaminobismaleimide; polyetheretherketone, and the like. Among these, from the viewpoints of dimensional stability and heat resistance, at least one selected from the group consisting of polyamide, liquid crystal polymer, PPS, and styrene-based polymers mainly having a syndiotactic structure is preferred, liquid crystal polymer and polyamide are more preferred, and polyamide is even more preferred. In the above-mentioned styrene-based polymer having a syndiotactic structure, the term "mainly" means that the syndiotactic structure accounts for, for example, 50 mol % or more, and further 60 mol % or more.

[0016] The melting point of the thermoplastic resin (A) is preferably 280° C. or higher, more preferably 285° C. or higher, and even more preferably 295° C. or higher. When the melting point of the thermoplastic resin (A) is within the above temperature range, a waterproof part containing the thermoplastic resin (A) can maintain sufficient waterproofness even when used in an application in which the waterproof part is exposed to a heating process such as a reflow process.

[0017] (polyamide) The polyamide preferably has a dicarboxylic acid unit and a diamine unit. Examples of the dicarboxylic acid unit include structural units derived from aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, dimethylmalonic acid, 2,2-diethylsuccinic acid, 2,2-dimethylglutaric acid, 2-methyladipic acid, and trimethyladipic acid; alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, cycloheptanedicarboxylic acid, cyclooctanedicarboxylic acid, and cyclodecanedicarboxylic acid; and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, diphenic acid, 4,4'-biphenyldicarboxylic acid, diphenylmethane-4,4'-dicarboxylic acid, and diphenylsulfone-4,4'-dicarboxylic acid. These units may be of one type or of two or more types. Furthermore, the polyamide may also contain structural units derived from trivalent or higher polyvalent carboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid to the extent that melt molding is possible, within the range that does not impair the effects of the present invention.

[0018] The polyamide is preferably one in which 50 to 100 mol % of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms, more preferably one in which 60 to 100 mol % of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms, and even more preferably one in which 90 to 100 mol % of the diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

[0019] Examples of the aliphatic diamine unit having 4 to 18 carbon atoms include 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,4-tetradecanediamine, 1,15-pentadecanediamine, 1,16-hexadecanediamine, 1,17-heptadecanediamine, and 1,18-octadecanediamine. linear aliphatic diamines such as 1,1-dimethyl-1,4-butanediamine, 1-ethyl-1,4-butanediamine, 1,2-dimethyl-1,4-butanediamine, 1,3-dimethyl-1,4-butanediamine, 1,4-dimethyl-1,4-butanediamine, 2,3-dimethyl-1,4-butanediamine, 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl-1,6-hexa- Sandiamine, 2,2-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-diethyl-1,6-hexanediamine, 2,2-dimethyl-1,7-heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 4-methyl-1 Examples of structural units include those derived from branched aliphatic diamines such as 1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine. These units may be of one type or two or more types. Among these, a structural unit derived from at least one selected from the group consisting of 1,4-butanediamine, 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,8-octanediamine, 2-methyl-1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine is preferred, and a structural unit derived from at least one selected from the group consisting of 1,4-butanediamine, 1,6-hexanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, and 1,10-decanediamine is more preferred.

[0020] When the diamine units contain both structural units derived from 1,9-nonanediamine and structural units derived from 2-methyl-1,8-octanediamine, the molar ratio of the structural units derived from 1,9-nonanediamine to the structural units derived from 2-methyl-1,8-octanediamine (structural units derived from 1,9-nonanediamine / structural units derived from 2-methyl-1,8-octanediamine) is preferably in the range of 95 / 5 to 40 / 60, and more preferably in the range of 90 / 10 to 50 / 50. Depending on the application, it may be preferable that the ratio of structural units derived from 1,9-nonanediamine / structural units derived from 2-methyl-1,8-octanediamine is in the range of 55 / 45 to 45 / 55.

[0021] The diamine unit in the polyamide may contain a diamine unit other than an aliphatic diamine unit having 4 to 18 carbon atoms, as long as the effect of the present invention is not impaired. Examples of such diamine units include constitutional units derived from aliphatic diamines such as ethylenediamine, 1,2-propanediamine, and 1,3-propanediamine; alicyclic diamines such as cyclohexanediamine, methylcyclohexanediamine, isophoronediamine, norbornanedimethylamine, and tricyclodecanedimethyldiamine; and aromatic diamines such as p-phenylenediamine, m-phenylenediamine, p-xylylenediamine, m-xylylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, and 4,4'-diaminodiphenylether. These units may be of one type or two or more types.

[0022] The polyamide may contain an aminocarboxylic acid unit. Examples of the aminocarboxylic acid unit include units derived from lactams such as caprolactam and lauryllactam; and aminocarboxylic acids such as 11-aminoundecanoic acid and 12-aminododecanoic acid. The content of the aminocarboxylic acid unit in the polyamide is preferably 40 mol% or less, more preferably 20 mol% or less, based on 100 mol% in total of the dicarboxylic acid unit and diamine unit of the polyamide.

[0023] The polyamide may contain units derived from a terminal blocking agent. The units derived from the terminal blocking agent are preferably 1.0 to 10 mol %, more preferably 2.0 to 7.5 mol %, and even more preferably 2.5 to 6.5 mol %, based on the diamine units. In order to adjust the units derived from the terminal blocking agent to the desired range, the amount of the terminal blocking agent relative to the diamine when the polymerization raw materials are charged can be adjusted to the desired range. In addition, taking into consideration that the monomer components volatilize during polymerization, it is desirable to finely adjust the amount of the terminal blocking agent charged when the polymerization raw materials are charged so that the desired amount of units derived from the terminal blocking agent is introduced into the resulting resin. The content of the units derived from the terminal blocking agent in the polyamide can be determined, for example, by measuring the solution viscosity, calculating the total amount of terminal groups from the relational equation between the viscosity and the number average molecular weight, and subtracting the amount of amino groups and the amount of carboxyl groups determined by titration, as described in JP-A-07-228690. 1 1H-NMR is used to determine the amount of the diamine unit and the amount of the end-capping agent based on the integral values ​​of the signals corresponding to the diamine unit and the unit derived from the end-capping agent.

[0024] As the terminal blocking agent, a monofunctional compound having reactivity with a terminal amino group or a terminal carboxyl group can be used.Specific examples thereof include monocarboxylic acid, acid anhydride, monoisocyanate, monoacid halide, monoester, monoalcohol, monoamine, etc. From the viewpoint of reactivity and the stability of the blocked end, a monocarboxylic acid is preferable as a terminal blocking agent for a terminal amino group, and a monoamine is preferable as a terminal blocking agent for a terminal carboxyl group.Moreover, from the viewpoint of ease of handling, etc., a monocarboxylic acid is more preferable as a terminal blocking agent.

[0025] The monocarboxylic acid used as the terminal blocking agent is not particularly limited as long as it is reactive with an amino group, and examples thereof include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclopentane carboxylic acid and cyclohexane carboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalene carboxylic acid, β-naphthalene carboxylic acid, methyl naphthalene carboxylic acid, and phenyl acetic acid; and any mixtures thereof. Among these, at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid is preferred from the standpoints of reactivity, stability of blocked terminals, and price.

[0026] The monoamine used as the terminal blocking agent is not particularly limited as long as it is reactive with a carboxyl group, and examples thereof include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, etc.; alicyclic monoamines such as cyclohexylamine, dicyclohexylamine, etc.; aromatic monoamines such as aniline, toluidine, diphenylamine, naphthylamine, etc.; any mixtures thereof, etc. Among these, at least one selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline is preferred in terms of reactivity, high boiling point, stability of blocked terminals, price, etc.

[0027] The polyamide can be produced by any method known as a method for producing polyamide, such as a solution polymerization method or an interfacial polymerization method using an acid chloride and a diamine as raw materials, a melt polymerization method, a solid-state polymerization method, and a melt extrusion polymerization method using a dicarboxylic acid and a diamine as raw materials.

[0028] The polyamide can be produced, for example, by first adding diamine, dicarboxylic acid, and if necessary, a catalyst or end-capping agent all at once to produce a nylon salt, then heating and polymerizing the prepolymer at a temperature of 200 to 250 ° C., and then further solid-phase polymerizing the prepolymer, or polymerizing the prepolymer using a melt extruder. When the final stage of polymerization is carried out by solid-phase polymerization, it is preferable to carry out the polymerization under reduced pressure or in an inert gas flow, and if the polymerization temperature is within the range of 200 to 280 ° C., the polymerization rate is high, productivity is excellent, and coloring and gelation can be effectively suppressed. When the final stage of polymerization is carried out using a melt extruder, the polymerization temperature is preferably 370 ° C. or less, and when polymerization is carried out under such conditions, a polyamide with almost no decomposition and little deterioration can be obtained.

[0029] Examples of catalysts that can be used in producing the polyamide include phosphoric acid, phosphorous acid, hypophosphorous acid, salts or esters thereof, etc. Examples of the salts or esters include salts of phosphoric acid, phosphorous acid or hypophosphorous acid with metals such as potassium, sodium, magnesium, vanadium, calcium, zinc, cobalt, manganese, tin, tungsten, germanium, titanium, and antimony; ammonium salts of phosphoric acid, phosphorous acid or hypophosphorous acid; ethyl esters, isopropyl esters, butyl esters, hexyl esters, isodecyl esters, octadecyl esters, decyl esters, stearyl esters, and phenyl esters of phosphoric acid, phosphorous acid or hypophosphorous acid.

[0030] The polyamide may be any of a crystalline polyamide, an amorphous polyamide, and a mixture thereof.

[0031] Examples of the crystalline polyamide include polycaproamide (polyamide 6), polyhexamethylene adipamide (polyamide 66), polytetramethylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polyundecamethylene adipamide (polyamide 116), polybis(4-aminocyclohexyl)methandecamide (polyamide PACM12), polybis(3-methyl-4-aminocyclohexyl)methandecamide (polyamide dimethyl PACM12), polyundecamethylene terephthalamide (polyamide 11T), polyundecamethylene hexahydroterephthalamide (polyamide 11), and the like. Examples of suitable polyamides include polyamide 6I and polyamide 6T (polyamide 6I / 6T), and polyamide 6T and polyundecaneamide (polyamide 11) (polyamide 12), polytrimethylhexamethylene terephthalamide (polyamide TMDT), polymetaxylylene adipamide (polyamide MXD6), polyhexamethylene terephthalamide (polyamide 6T), polynonamethylene terephthalamide (polyamide 9T), polydecamethylene terephthalamide (polyamide 10T), polyhexamethylene isophthalamide (polyamide 6I), a copolymer of polyamide 6I and polyamide 6T (polyamide 6I / 6T), and a copolymer of polyamide 6T and polyundecaneamide (polyamide 11) (polyamide 6T / 11), as well as copolymers and mixtures thereof. The polyamide 9T also includes polyamide 9T in which the diamine units are 1,9-nonanediamine units and 2-methyl-1,8-octanediamine units (molar ratio 50 / 50 to 99.9 / 0.1). The crystalline polyamide also includes those in which the benzene rings of terephthalic acid and / or isophthalic acid are substituted with alkyl groups or halogen atoms. Among the crystalline polyamides, polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are preferred, polyamide 6, polyamide 66, polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are more preferred, and polyamide 46, polyamide 6T, polyamide 9T, and polyamide 10T are even more preferred. The crystalline polyamides may be used alone or in combination of two or more of the above.

[0032] Examples of the amorphous polyamide include a polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine, a polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane, a polycondensate of terephthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine, a polycondensate of isophthalic acid / bis(3-methyl-4-aminocyclohexyl)methane / ω-laurolactam, a polycondensate of isophthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine, and a polycondensate of terephthalic acid / isophthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine. The amorphous polyamide also includes those in which the benzene ring of terephthalic acid and / or isophthalic acid is substituted with an alkyl group or a halogen atom. Among the amorphous polyamides, the polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine, the polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane, and the polycondensate of terephthalic acid / 2,2,4-trimethyl-1,6-hexanediamine / 2,4,4-trimethyl-1,6-hexanediamine are preferred, and the polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine and the polycondensate of terephthalic acid / isophthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane are more preferred. The amorphous polyamides may be used alone or in combination of two or more of the above.

[0033] (Inorganic reinforcement (B)) Examples of the inorganic reinforcing material (B) used in the present invention include glass fibers, milled fibers, cut fibers, wollastonite, potassium titanate whiskers, calcium carbonate whiskers, aluminum borate whiskers, magnesium sulfate whiskers, sepiolite, xonotlite, zinc oxide whiskers, glass beads, spherical silica, glass balloons, shirasu balloons, titanium oxide, carbon black, mica, glass flakes, kaolin, talc, and layered silicates, etc. These may be used alone or in combination of two or more. Among the inorganic reinforcing materials (B), at least one selected from the group consisting of glass fiber, milled fiber, wollastonite, mica, glass flakes, and glass beads is preferred, at least one selected from the group consisting of milled fiber, wollastonite, and mica is more preferred, and at least one selected from the group consisting of milled fiber and wollastonite is even more preferred.

[0034] The inorganic reinforcing material (B) is preferably in the form of fibers. When the inorganic reinforcing material (B) is fibrous, from the viewpoint of waterproofness, the average fiber diameter is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 7 μm or less, and from the viewpoint of strength, the average fiber diameter is preferably 2 μm or more, more preferably 4 μm or more. From the viewpoint of waterproofness, the average fiber length is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, and even more preferably 1500 μm or less. From the viewpoint of strength, the average fiber length is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more. The average fiber diameter and the average fiber length are those before melt-kneading.

[0035] In this specification, the "average fiber diameter" refers to the fiber diameter at 50% cumulative mass, and can be measured by dispersing the inorganic reinforcing material (B) in a 0.2% aqueous solution of sodium metaphosphate and using a particle size distribution measuring device (such as "SediGraph III 5120" manufactured by Micromeritics Instrument Corp.) by X-ray transmission gravity sedimentation method.

[0036] In addition, the "average fiber length" in this specification can be determined by measuring the fiber lengths of 400 arbitrarily selected inorganic reinforcing materials (B) by image analysis using an electron microscope, and calculating the weight average value.

[0037] As the inorganic reinforcing material (B), either or both of glass fibers having a circular cross section and glass fibers having a noncircular cross section can be used. When glass fibers having a circular cross section and glass fibers having a noncircular cross section are used in combination, the ratio of their contents is not particularly limited, but the circular cross section / noncircular cross section ratio is preferably 20 / 80 to 80 / 20, more preferably 30 / 70 to 60 / 40, and even more preferably 30 / 70 to 50 / 50.

[0038] The cross-sectional shape of the glass fiber having a circular cross section is, for example, a perfect circle or a nearly circular shape, while the cross-sectional shape of the glass fiber having a non-circular cross section is, for example, a cocoon shape with a narrowed central portion in the longitudinal direction of the cross section, an oval shape having a portion that is nearly parallel to the center of gravity of the cross section at a symmetrical position, or an ellipse. From the viewpoints of the flame retardancy and mechanical strength of the resulting molded product, it is preferable that the inorganic reinforcing material (B) is at least one type selected from glass fibers having circular and noncircular cross sections, and that the circumferential length of the cross section of the glass fiber having a noncircular cross section is 1.05 to 1.8 times the circumferential length of the glass fiber having a circular cross section with the same cross-sectional area as the noncircular cross section.

[0039] The content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, preferably 40 to 130 parts by mass, and more preferably 45 to 110 parts by mass, per 100 parts by mass of the thermoplastic resin (A). If the content of the inorganic reinforcing material (B) is less than 8 parts by mass, the inorganic reinforcing material (B) will not provide sufficient reinforcing effect and will not provide waterproofing effect, and if the content of the inorganic reinforcing material (B) exceeds 130 parts by mass, melt-kneadability will be poor.

[0040] (Olefin Compounds (C)) The thermoplastic resin composition contains a polyolefin (C1) and / or a long-chain fatty acid compound (C2). That is, the thermoplastic resin may contain either one of the polyolefin (C1) and the long-chain fatty acid compound (C2), or may contain both. In this specification, "polyolefin (C1) and / or long-chain fatty acid compound (C2)" may be referred to as "olefin compound (C)". (Polyolefin (C1)) Specific examples of the polyolefin (C1) include polyethylene, polypropylene, vinyl acetate-ethylene copolymers, and modified polyolefins obtained by partially modifying these with reactive functional groups such as oxidation or maleic acid. Additionally, these polyolefins may be high or low density and may be metallocene catalyzed. More specifically, among the polyolefins (C1), at least one homopolymer selected from the group consisting of polyethylene and polypropylene is preferred. Moreover, these polyolefins preferably have a molecular weight of 1,000 or more, and more preferably have a molecular weight of 5,000 or more.

[0041] In order to improve compatibility with the thermoplastic resin (A), prevent the polyolefin (C1) from falling off from the surface of the insert molded article, and improve the surface properties and moldability, it is preferable that the polyolefin (C1) is partially oxidized or modified with a reactive functional group such as maleic acid. That is, the polyolefin (C1) is preferably a polyolefin that has been modified with at least one of maleic acid modification, oxidation, and polar monomer modification, more preferably at least one selected from the group consisting of modified polyethylene and modified polypropylene partially modified with oxidation or reactive functional groups of maleic acid, and even more preferably at least one selected from the group consisting of modified polyethylene and modified polypropylene modified with maleic anhydride. The modified polyolefins include modified polyolefin waxes such as modified polyethylene wax and modified polypropylene wax. Moreover, it is preferable that the resin composition is substantially free of elastomers or ionomers, since these may cause a decrease in the heat resistance and mechanical strength of the molded product and may increase flash in the insert molded product.

[0042] (Long-chain fatty acid compounds (C2)) The long-chain fatty acid compound (C2) is preferably a long-chain fatty acid compound having 15 or more carbon atoms, and examples thereof include metal salts such as calcium salts of higher fatty acids such as palmitic acid, stearic acid, behenic acid, montanic acid, rice bran wax, esters, and mixtures thereof. Among the long-chain fatty acid compounds (C2), at least one selected from the group consisting of metal salts, esters, and mixtures thereof of saturated aliphatic monocarboxylic acids having 15 or more carbon atoms is preferred, at least one selected from the group consisting of metal salts, esters, and mixtures thereof of saturated aliphatic monocarboxylic acids having 20 or more carbon atoms is more preferred, and at least one selected from the group consisting of metal salts, esters, and mixtures thereof of montanic acid is even more preferred. It is also preferred that the long-chain fatty acid compound (C2) is a long-chain fatty acid compound having 15 or more carbon atoms and that has been subjected to at least one modification treatment selected from the group consisting of esterification, maleic acid modification, and saponification.

[0043] The content of the polyolefin (C1) and the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, preferably 0.5 parts by mass or more, may be 1.5 parts by mass or more, or may be 2.0 parts by mass or more, relative to 100 parts by mass of the thermoplastic resin (A). The content of the polyolefin (C1) and the long-chain fatty acid compound (C2) is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and may be 20 parts by mass or less, 15 parts by mass or less, or 10 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin (A). If the content of the polyolefin (C1) and the long-chain fatty acid compound (C2) is less than 0.3 parts by mass, a sufficient waterproof effect cannot be obtained, and if the content of each of them exceeds 40 parts by mass, the moldability of the thermoplastic resin composition is poor. When the polyolefin (C1) and the long-chain fatty acid compound (C2) are used in combination, the above content is the total content of the polyolefin (C1) and the long-chain fatty acid compound (C2).

[0044] [Phosphinate (D)] The thermoplastic resin composition contains the phosphinate (D) and can be a halogen-free thermoplastic resin composition that provides an insert molding having excellent flame retardancy. When a flame retardant other than the phosphinate (D) and the phosphite (E) described below is used, it becomes difficult to withstand high molding temperatures, and there is a risk that excellent waterproofing cannot be obtained. The phosphinate (D) is at least one type represented by the following formula (I) or the following formula (II). That is, the phosphinate (D) is a phosphinate represented by the following formula (I), a diphosphinate represented by the following formula (II), or a mixture thereof.

[0045] [ka]

[0046] [ka]

[0047] In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a straight or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. Among them, an alkyl group having 1 to 8 carbon atoms is preferable, and a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, an n-pentyl group, or an n-octyl group is more preferable, and an ethyl group is even more preferable. Examples of the aryl group having 6 to 10 carbon atoms include a phenyl group and a naphthyl group. R 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. R 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. Examples of the linear or branched alkylene group having 1 to 10 carbon atoms include a methylene group, an ethylene group, an n-propylene group, an isopropylene group, an isopropylidene group, an n-butylene group, a tert-butylene group, an n-pentylene group, and an n-octylene group. Examples of the arylene group having 6 to 10 carbon atoms include a phenylene group and a naphthylene group. Examples of the alkylarylene group having 7 to 10 carbon atoms include a methylphenylene group, an ethylphenylene group, a tert-butylphenylene group, a methylnaphthylene group, an ethylnaphthylene group, and a tert-butylnaphthylene group. Examples of the cycloalkylene group having 3 to 10 carbon atoms include a cyclohexylene group and a cyclohexadimethylene group. Examples of the aralkylene group having 7 to 10 carbon atoms include a phenylenemethylene group, a phenyleneethylene group, and a xylylene group. Examples of the arylalkylene group having 7 to 20 carbon atoms include a phenylmethylene group, a phenylethylene group, a phenylpropylene group, and a phenylbutylene group. M represents calcium, aluminum, magnesium, or zinc, with aluminum and zinc being preferred, and aluminum being more preferred. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n (i.e., the product of m and x is equal to the product of 2 and n).

[0048] Examples of the phosphinic acid constituting the phosphinic acid salt (D) include dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylphosphinic acid, isobutylmethylphosphinic acid, octylmethylphosphinic acid, methylphenylphosphinic acid, and diphenylphosphinic acid. Among these, diethylphosphinic acid is preferred.

[0049] Specific examples of the phosphinate represented by the above formula (I) include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate.

[0050] Examples of the diphosphinic acid constituting the diphosphinic acid salt represented by the above formula (II) include methane di(methylphosphinic acid) and benzene-1,4-di(methylphosphinic acid). Specific examples of diphosphinates include calcium methane di(methylphosphinate), magnesium methane di(methylphosphinate), aluminum methane di(methylphosphinate), zinc methane di(methylphosphinate), calcium benzene-1,4-di(methylphosphinate), magnesium benzene-1,4-di(methylphosphinate), aluminum benzene-1,4-di(methylphosphinate), and zinc benzene-1,4-di(methylphosphinate).

[0051] As the phosphinate (D), from the viewpoint of even more excellent flame retardancy, aluminum diethylphosphinate, zinc diethylphosphinate, aluminum methane di(methylphosphinate), and zinc methane di(methylphosphinate) are preferred, and among these, aluminum diethylphosphinate is more preferred.

[0052] The number average particle size of the phosphinic acid salt (D) is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 40 μm or less, from the viewpoint of the flame retardancy, waterproofness, mechanical strength, and appearance of the obtained insert molding. The lower limit of the number average particle size is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. By using a powder having a number average particle size in the above range, not only can higher flame retardancy be exhibited, but also the mechanical strength of the obtained molded article can be increased. The number average particle size is the particle size value at 50% cumulative weight when the particle size distribution is measured using a particle size distribution measuring device such as a laser scattering particle size distribution meter.

[0053] The thermoplastic resin composition contains 25 to 40 parts by mass of the phosphinate (D) relative to 100 parts by mass of the thermoplastic resin (A). If the content of the phosphinate (D) is less than 25 parts by mass, it is difficult for the insert molded article to exhibit excellent flame retardancy. If the content exceeds 40 parts by mass, the thermoplastic resin composition may be inferior in moldability and mechanical strength. The content of the phosphinate (D) is preferably 26 parts by mass or more, more preferably 27 parts by mass or more. The content of the phosphinate (D) is preferably 38 parts by mass or less, more preferably 35 parts by mass or less.

[0054] [Phosphite (E)] By containing the phosphite (E), the thermoplastic resin composition can exhibit excellent flame retardancy, and further the melt-kneading and molding processability of the thermoplastic resin composition becomes good. The phosphites (E) are not particularly limited, but examples thereof include sodium phosphite, potassium phosphite, calcium phosphite, zinc phosphite, ammonium phosphite, aluminum phosphite, and aluminum hydrogen phosphite. From the viewpoint of exhibiting even more excellent flame retardancy, aluminum phosphite and aluminum hydrogen phosphite are preferred. The phosphites may be used alone or in combination of two or more.

[0055] The thermoplastic resin composition contains 2 to 15 parts by mass of the phosphite (E) per 100 parts by mass of the thermoplastic resin (A). If the content of the phosphite (E) is less than 2 parts by mass, it becomes difficult for the insert molded article to exhibit excellent flame retardancy. If the content exceeds 15 parts by mass, the thermoplastic resin composition may be inferior in moldability, waterproofness, and mechanical strength. The content of the phosphite (E) is preferably 2.5 parts by mass or more, more preferably 3 parts by mass or more. The content of the phosphite (E) is preferably 13 parts by mass or less, more preferably 10 parts by mass or less.

[0056] In the thermoplastic resin composition, the total amount of the phosphinate (D) and the phosphite (E) is preferably 16 to 25% by mass relative to 100% by mass of the thermoplastic resin composition from the viewpoints of flame retardancy, mechanical strength, and moldability. The total amount is more preferably 16.5% by mass or more, and even more preferably 17% by mass or more. The total amount is more preferably 23% by mass or less, and even more preferably 22.5% by mass or less.

[0057] In the thermoplastic resin composition, the mass ratio (D) / (E) of the phosphinate (D) to the phosphite (E) is preferably 70 / 30 to 94 / 6 from the viewpoint of flame retardancy, more preferably 75 / 25 to 93 / 7, and further preferably 80 / 20 to 92 / 8.

[0058] The total content of the thermoplastic resin (A), inorganic reinforcing material (B), polyolefin (C), phosphinate (D), and phosphite (E) is preferably 90 to 99.9 mass%, more preferably 95 to 99.9 mass%, and even more preferably 95 to 99.5 mass%, based on 100 mass% of the thermoplastic resin composition. If the total content is within the above range, the thermoplastic resin composition can provide an insert molding having even more excellent flame retardancy and waterproofness.

[0059] (Other Ingredients) The thermoplastic resin composition used in the present invention may further contain other components, such as a heat stabilizer, a light stabilizer, a styrene-maleic anhydride copolymer (SMA), a lubricant, a nucleating agent, a crystallization retarder, a hydrolysis inhibitor, an antistatic agent, a radical inhibitor, a matting agent, an ultraviolet absorber, a viscosity reducer, an anti-drip agent, an agent for imparting sliding properties, and inorganic substances other than the inorganic reinforcing material (B), in addition to the thermoplastic resin (A), the inorganic reinforcing material (B), within a range that does not impair the effects of the present invention. Examples of the inorganic substances used other than inorganic reinforcing materials include carbon nanotubes, fullerenes, talc, zeolite, sericite, kaolin, clay, pyrophyllite, silica, bentonite, alumina silicate, silicon oxide, magnesium oxide, alumina, zirconium oxide, titanium oxide, iron oxide, calcium carbonate, magnesium carbonate, dolomite, calcium sulfate, barium sulfate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, glass powder, ceramic beads, boron nitride, silicon carbide, carbon black, graphite, and various clay minerals such as halloysite and vermiculite. The content of other components in the thermoplastic resin composition can be, for example, 50% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. When other components are included, the content can be, for example, 0.1% by mass or more.

[0060] (Metal parts) The metal constituting the metal part used in the present invention is not particularly limited as long as it can be insert molded, and examples thereof include aluminum, copper, iron, tin, nickel, zinc, copper alloys, aluminum alloys, and alloys such as stainless steel, etc. The surfaces of these may be plated with aluminum, tin, nickel, gold, silver, zinc, tin, etc.

[0061] (Waterproof parts) Waterproof parts are The composition comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), a phosphinate (D), and a phosphite (E), The thermoplastic resin composition can be produced by insert molding a metal part with a thermoplastic resin composition obtained by melt-kneading 100 parts by mass of the thermoplastic resin (A), 8 to 130 parts by mass of the inorganic reinforcing material (B), and 0.3 to 40 parts by mass of the polyolefin (C1) and / or the long-chain fatty acid compound (C2). The phosphinate (D) is at least one type represented by formula (I) or formula (II) as described above. In the insert molding, any method known as an insert molding method, such as an injection insert molding method or a compression insert molding method, can be used. If necessary, after the insert molding, further processing such as ultrasonic welding, laser welding, vibration welding, heat welding, hot melt welding, etc. may be carried out.

[0062] In component mounting for mounting electronic components on a printed circuit board, an insertion mounting process has been applied in which soldering is performed by immersing the components in a molten solder bath (dip bath). On the other hand, in surface mounting, which has been increasingly used in recent years, a solder paste is printed on a printed circuit board, electronic components are mounted on it, and then the solder is melted by heating in a reflow furnace at about 260°C to bond the printed circuit board and the electronic components. Surface mounting can achieve miniaturization of printed circuit boards and improvement of productivity, but in the reflow process and the subsequent cooling process, stress is generated in the mounted components according to the difference in expansion and contraction characteristics between the metal components and the resin or resin composition, and minute gaps are likely to occur between the metal components and the resin or resin composition, making it difficult to maintain waterproofness. The waterproof component of the present invention is not easily deformed even after undergoing a heating process such as a reflow process, so it is preferable to use it for applications applied to surface mounting processes in which such a reflow process is adopted. In addition, a heating process such as a reflow process may be applied multiple times as necessary.

[0063] Since the waterproof component of the present invention has excellent waterproof properties, it is useful as external connection terminals such as FPC connectors, BtoB connectors, card connectors, SMT connectors (coaxial connectors, etc.), memory card connectors, etc.; SMT relays; SMT bobbins; sockets such as memory sockets and CPU sockets; switches such as command switches and SMT switches; sensors such as rotation sensors and acceleration sensors, etc., and among these, it is useful as switches or external connection terminals for electronic devices, and is particularly useful as switches. When the waterproof part of the present invention is used as a switch, the outer dimensions of the insert molded product consisting of a thermoplastic resin composition and a metal part are width x depth x thickness, and the width is preferably 15 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less, the depth is preferably 50 mm or less, more preferably 25 mm or less, and even more preferably 5 mm or less, and the thickness is preferably 50 mm or less, more preferably 15 mm or less, and even more preferably 3 mm or less. Note that the depth of the outer dimensions is longer than the width. By using the waterproof component of the present invention, particularly as a switch or an external connection terminal, electronic devices can be effectively waterproofed. Examples of electronic devices equipped with the waterproof component of the present invention include, but are not limited to, portable electronic devices such as digital cameras and smartphones. That is, the present invention can also provide a waterproofing method using an insert molded article made of the above-mentioned thermoplastic resin composition and metal part, and use of the insert molded article for waterproofing. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way. The melting point and glass transition temperature of the thermoplastic resin (A) used in the examples and comparative examples were measured according to the methods described below.

[0065] (Melting point and glass transition temperature of thermoplastic resin (A)) The melting point of the polyamide (PA9T described later) used as the thermoplastic resin (A) was determined by measuring the peak temperature of the melting peak that appeared when the temperature was raised from 30° C. to 360° C. at a rate of 10° C. / min under a nitrogen atmosphere using a differential scanning calorimeter (DSC7020) manufactured by Hitachi High-Tech Science Corp. When there were multiple melting peaks, the peak temperature of the melting peak on the highest temperature side was determined as the melting point. The sample was then kept at a temperature 30°C higher than the melting point for 10 minutes to completely melt it, then cooled to 40°C at a rate of 10°C / min and kept at 40°C for 10 minutes. The temperature was then raised again to a temperature 30°C higher than the melting point at a rate of 10°C / min, and the midpoint at which the DSC curve changed in a stepwise manner was taken as the glass transition temperature.

[0066] [Examples 1 to 4 and Comparative Examples 1 to 3] The thermoplastic resin (A), olefinic compound (C), phosphinic acid salt (D), phosphite (E), and other components shown in Table 1 were fed from the most upstream hopper to a twin-screw extruder (screw diameter 32 mmφ, L / D=30, rotation speed 150 rpm, discharge rate 10 kg / h) manufactured by the Plastics Engineering Research Institute, and the inorganic reinforcing material (B) shown in Table 1 was further fed from a side feeder and melt-kneaded. The melt-kneaded thermoplastic resin composition was extruded in the form of a strand, cooled, and then cut to obtain pellets of the thermoplastic resin composition. The amounts of the thermoplastic resin (A), inorganic reinforcing material (B), olefinic compound (C), phosphinic acid salt (D), phosphite (E), and other components in Table 1 all mean "parts by mass." These pellets were used to prepare molded articles (insert molded articles) and were evaluated by the following method.

[0067] [Red ink test (waterproof test)] Using an injection molding machine TR40EH manufactured by Sodick Co., Ltd., the thermoplastic resin composition obtained in each Example or Comparative Example was injection molded into a box shape (outside dimensions: width 2.8 mm, depth 3.0 mm, thickness 1.3 mm) on an LED lead frame made of silver-plated copper base material at a maximum temperature of 320°C, a mold temperature of 140°C, and an injection speed of 100 to 200 mm / s. The flat molded product obtained above was subjected to heat treatment twice under the following reflow conditions using a reflow device with a maximum temperature of 260°C, and the following red ink test was carried out using the sample. Here, FIG. 1 is a photograph of the surface of the sample. Also, FIG. 2 is a schematic diagram showing a cross-sectional view of the X-X' line of the sample photograph of FIG. 1. As shown in FIG. 2, the sample is an insert molding consisting of an LED lead frame 1 and a box mold 2 formed of a thermoplastic resin composition, and has a depression 3 for ink dropping to be used in a red ink test. The depression portion has a non-connected portion 4 where a part of the LED lead frame is exposed and a part of the LED lead frame is missing. Also, the box mold 2 has a gap 5 on the back side (the surface not having the depression 3), but the non-connected portion 4 and the gap 5 do not overlap. In addition, a ring-shaped portion is shown in the box mold 2 in the photograph of FIG. 1, but this is because the curved part of the thermoplastic resin composition reflects light and looks ring-shaped. (Reflow conditions): The sample was heated from 25°C to 150°C over 60 seconds, then heated to 180°C over 90 seconds, and further heated to 260°C over 60 seconds. After being held at 260°C for 20 seconds, the sample was cooled from 260°C to 100°C over 30 seconds, and after reaching 100°C, air was sealed in and the sample was allowed to cool naturally to 23°C. (Red ink test): Red ink (PILOT CORPORATION, fountain pen ink INK-30-RED) was dropped into the recessed portion of the box-shaped thermoplastic resin composition, and after leaving it for 10 minutes, the ink was removed. The box-shaped (thermoplastic resin composition) was then removed from the LED lead frame, and it was confirmed whether the ink was attached to the back side of the LED lead frame, which is the side opposite to the ink drop side. (Evaluation Criteria) As an evaluation criterion for the ink leakage, the amount of ink remaining in the recess was measured, and the ratio of the amount of ink remaining in the recess to the amount of ink dropped was calculated (mass %). The calculated value was evaluated according to the following evaluation criteria. A: More than 99% by mass to 100% by mass B: More than 60% by mass and less than 99% by mass C: More than 30% by mass to less than 60% by mass D: More than 0% by mass to less than 30% by mass E:0 mass% In addition, (3-1) in Fig. 3 is a photograph of the sample surface, with the left one before the red ink was applied and the right one after the red ink was applied. (3-2) in Fig. 3 is a photograph of the back surface of the sample before the red ink was applied. (3-3) in Fig. 3 is a photograph showing the results of Example 1 after the red ink test. (3-4) in Fig. 3 is a photograph showing the results of Comparative Example 1 after the red ink test.

[0068] [Flame retardancy] Using an injection molding machine UH-1000 manufactured by Nissei Plastic Industrial Co., Ltd., pellets of the thermoplastic resin composition obtained in each Example or Comparative Example were injection molded into plate-shaped test pieces (thicknesses of 0.40 mm and 0.75 mm) having a width of 12.5 mm and a length of 125 mm at a maximum cylinder temperature of 320° C., a mold temperature of 140° C., and an injection speed of 750 to 150 mm / s. The test pieces of each thickness were evaluated for flame retardancy in accordance with the provisions of the UL94 standard shown below. <UL94 Standards - Flame Retardancy Test> The upper end of the test piece is clamped to hold it vertically, and a specified flame is applied to the lower end for 10 seconds and then released, measuring the burning time of the test piece (first time). Once the flame is out, the flame is immediately applied to the lower end again for 10 seconds and then released, measuring the burning time of the test piece (second time). The same measurement is repeated for five pieces, obtaining a total of ten pieces of data: five data points for the first burning time and five data points for the second burning time. The sum of the ten data points is T, and the maximum value of the ten data points is M. If T is less than 50 seconds, M is less than 10 seconds, the flame does not reach the clamp, and the flaming molten material does not fall and ignite the dry cotton set 12 inches below, it is rated "V-0". If T is less than 250 seconds, M is less than 30 seconds, and all other conditions are the same as V-0, it is rated "V-1". If T is less than 250 seconds, M is less than 30 seconds, the flame does not reach the clamp, and the flaming molten material falls and ignites the cotton set 12 inches below, it is rated "V-2".

[0069] [Table 1]

[0070] The components shown in Table 1 are as follows. [Thermoplastic resin (A)] PA9T: "Genestar GC51010", manufactured by Kuraray Co., Ltd., PA9T (a polyamide in which the dicarboxylic acid unit is a terephthalic acid unit and the diamine unit is a 1,9-nonanediamine unit and a 2-methyl-1,8-octanediamine unit (molar ratio 85 / 15)), melting point 305°C, glass transition temperature 125°C [Inorganic reinforcement (B)] Glass fiber: "T-262", manufactured by Nippon Electric Glass Co., Ltd., average fiber diameter 10 μm, average fiber length 3 mm [Olefin compounds (C)] (Polyolefin (C1)) Maleic acid modified polypropylene: "LICOCENE PP MA6252", Clariant Chemicals Co., Ltd., polypropylene wax modified with maleic anhydride [Phosphinate (D)] Aluminum phosphinate: "Exolit OP 1230" (Clariant Chemicals, aluminum diethylphosphinate, number average particle size 25 μm) [Phosphite (E)] Aluminum phosphite: "APA-100" (manufactured by Taihei Chemical Industry Co., Ltd., aluminum phosphite) [Other ingredients] Antioxidant-1: "Irganox1098", manufactured by BASF Japan Ltd. Antioxidant-2: "Irgafos168", manufactured by BASF Japan Ltd. Release agent-1: High density polyethylene "HI WAX 200P", manufactured by Mitsui Chemicals, Inc. Release agent-2: High density polyethylene "HI WAX NP055", manufactured by Mitsui Chemicals, Inc. Viscosity reducer: Calcium stearate "Calcium Stearate S", NOF Corporation Anti-drip agent: Styrene-maleic anhydride copolymer "XIBOND SZ23110", manufactured by Polyscope Nucleating agent: Carbon black "#980B", manufactured by Mitsubishi Chemical Corporation

[0071] In Example 1, as shown in (3-3) of FIG. 3, no red ink was attached to the back surface of the LED lead frame after the resin composition was removed. In Example 1, even after the reflow process, no gap was generated between the LED lead frame and the thermoplastic resin composition, and it is understood that an insert molded article with excellent waterproof properties was obtained. In addition, the resin composition in Example 1 obtained excellent results in the flame retardancy test. In addition, in Examples 2 to 4, similar results to Example 1 were obtained, and it is understood that an insert molded article with excellent waterproof properties and flame retardancy was obtained. On the other hand, in Comparative Example 1, as shown in (3-4) of FIG. 3, red ink was attached to the back surface of the LED lead frame after removing the resin composition. That is, in Comparative Example 1, since the thermoplastic resin composition does not contain the olefin-based compound (C), a gap was generated between the LED lead frame and the thermoplastic resin composition by the reflow process, and it is considered that the red ink entered from the unconnected portion 4 and leaked out, resulting in poor waterproofing. In Comparative Example 2, since the content of the olefin-based compound (C) in the thermoplastic resin composition was too small, a gap was generated between the LED lead frame and the thermoplastic resin composition by the reflow process, resulting in poor waterproofing. In Comparative Example 3, since the thermoplastic resin composition does not contain the olefin-based compound (C), a gap was generated between the LED lead frame and the thermoplastic resin composition by the reflow process, similar to Comparative Example 2, resulting in poor waterproofing. Therefore, by comparing the Examples and Comparative Examples, it is evident that the waterproof part of the present invention has excellent waterproofness and flame retardancy after the reflow process. [Industrial Applicability]

[0072] According to the present invention, it is possible to provide a waterproof part that is an insert molded body having sufficient waterproofness and excellent flame retardancy even after undergoing a heating process such as a reflow process. The waterproof part is particularly useful as an external connection terminal of an electronic device. [Explanation of symbols]

[0073] 1. LED lead frame (metal part) 2. Box mold made of thermoplastic resin composition 3. Ink drip recess 4.Discontinuous parts of LED lead frames 5. Gap

Claims

1. A waterproof part which is an insert molding made of a thermoplastic resin composition and a metal part, The thermoplastic resin composition comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the following formula (I) or the following formula (II), and a phosphite (E), A waterproof part, wherein, relative to 100 parts by mass of the thermoplastic resin (A), the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass. 【Chemistry 1】 【Chemistry 2】 [In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n.]

2. The waterproof part according to claim 1, wherein the polyolefin (C1) is a polyolefin that has been subjected to at least one of maleic acid modification, oxidation, and polar monomer modification.

3. The waterproof part according to claim 1 or 2, wherein the long-chain fatty acid compound (C2) is a long-chain fatty acid compound having 15 or more carbon atoms.

4. The waterproof part according to any one of claims 1 to 3, wherein the long-chain fatty acid compound (C2) is a long-chain fatty acid compound having 15 or more carbon atoms and has been subjected to at least one modification treatment selected from the group consisting of esterification, maleic acid modification, and saponification.

5. The waterproof part according to any one of claims 1 to 4, wherein the phosphite (E) is aluminum phosphite or aluminum hydrogen phosphite.

6. The waterproof part according to any one of claims 1 to 5, wherein the melting point of the thermoplastic resin (A) is 280°C or higher.

7. The waterproof part according to any one of claims 1 to 6, wherein the thermoplastic resin (A) is at least one selected from the group consisting of polyamide, liquid crystal polymer, polyphenylene sulfide, and a styrene-based polymer having a mainly syndiotactic structure.

8. The waterproof part according to any one of claims 1 to 7, wherein the thermoplastic resin (A) is a polyamide in which 50 to 100 mol % of diamine units are aliphatic diamine units having 4 to 18 carbon atoms.

9. The waterproof part according to any one of claims 1 to 8, wherein the inorganic reinforcing material (B) is at least one selected from the group consisting of glass fiber, milled fiber, wollastonite, mica, glass flakes, and glass beads.

10. The waterproof part according to any one of claims 1 to 9, wherein the inorganic reinforcing material (B) is at least one type selected from glass fibers having a circular cross section and a noncircular cross section, and the peripheral length of a cross section of the glass fiber having a noncircular cross section is 1.05 to 1.8 times the peripheral length of a glass fiber having the circular cross section and having the same cross-sectional area as the noncircular cross section.

11. The waterproof part according to any one of claims 1 to 10, which is used in an application applied to a surface mounting process.

12. The waterproof part according to any one of claims 1 to 11, which is an external connection terminal.

13. The waterproof part according to any one of claims 1 to 11, which is a switch.

14. An electronic device comprising the waterproof component according to any one of claims 1 to 13.

15. 15. The electronic device of claim 14, which is a portable electronic device.

16. The present invention comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the following formula (I) or the following formula (II), and a phosphite (E), A thermoplastic resin composition is used in which the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A). A method for waterproofing an electronic device using an insert molded article comprising the thermoplastic resin composition and a metal part. 【Chemistry 3】 【Chemistry 4】 [In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n.]

17. The present invention comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the following formula (I) or the following formula (II), and a phosphite (E), A thermoplastic resin composition is used in which the content of the inorganic reinforcing material (B) is 8 to 130 parts by mass, the content of the polyolefin (C1) and / or the long-chain fatty acid compound (C2) is 0.3 to 40 parts by mass, the content of the phosphinate (D) is 25 to 40 parts by mass, and the content of the phosphite (E) is 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A). Use of the thermoplastic resin composition and a metal part as an insert molding for waterproofing. 【Chemistry 5】 【Chemistry 6】 [In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n.]

18. A method for waterproofing an electronic device, comprising using the waterproof part according to any one of claims 1 to 11 as an external connection terminal.

19. A method for waterproofing an electronic device, comprising using the waterproof component according to any one of claims 1 to 11 as a switch.

20. The present invention comprises a thermoplastic resin (A), an inorganic reinforcing material (B), a polyolefin (C1) and / or a long-chain fatty acid compound (C2), at least one phosphinate (D) represented by the following formula (I) or the following formula (II), and a phosphite (E), A method for producing a waterproof part, comprising insert-molding a thermoplastic resin composition, the content of which is 8 to 130 parts by mass of the inorganic reinforcing material (B), the content of which is 0.3 to 40 parts by mass of the polyolefin (C1) and / or the long-chain fatty acid compound (C2), the content of the phosphinate (D) being 25 to 40 parts by mass, and the content of the phosphite (E) being 2 to 15 parts by mass, relative to 100 parts by mass of the thermoplastic resin (A), with a metal part. 【Chemistry 7】 【Chemistry 8】 [In formula (I) and formula (II), R 1 , R 2 , R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 16 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 1 and R 2 and R 4 and R 5 may be bonded to each other to form a ring. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 20 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, an aralkylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 20 carbon atoms. M represents calcium, magnesium, aluminum, or zinc. m is an integer of 1 to 4. n is an integer of 1 to 4. x is an integer of 1 to 4. In formula (II), m, x, and n satisfy the relational formula mx=2n.]

Citation Information

Patent Citations

  • Nannenseihoriamidoseikeizairyo

    JP1976063859A

  • Waterproof connector

    JP2002033155A

  • Heat-resistant resin composition

    JP2007182550A

  • Excellently heat-resistant resin composition

    JP2007182551A

  • Lightweight parts with a hybrid structure

    JP2010520820A